Direct and Indirect Transcriptional Effects of Abiotic Stress in Zea mays Plants Defective in RNA-Directed DNA Methylation - Madzima, Thelma F.; Vendramin, Stefania; Lynn, Jason S.; Lemert, Phebe; Lu, Katherine C.; McGinnis, Karen M. (Frontiers in Plant Science, 2021)
Plants respond to abiotic stress stimuli, such as water deprivation, through a hierarchical cascade that includes detection and signaling to mediate transcriptional and physiological changes. The phytohormone abscisic acid (ABA) is well-characterized for its regulatory role in these processes in response to specific environmental cues. ABA-mediated changes in gene expression have been demonstrated to be temporally-dependent, however, the genome-wide timing of these responses are not well characterized in the agronomically important crop plant Zea mays (maize). ABA-mediated responses are synergistic with other regulatory mechanisms, including the plant-specific RNA-directed DNA methylation (RdDM) epigenetic pathway. Our prior work demonstrated that after relatively long-term ABA induction (8 hours), maize plants homozygous for the mop1-1 mutation, defective in a component of the RdDM pathway, exhibit enhanced transcriptional sensitivity to the phytohormone. At this time-point, many hierarchically positioned transcription factors are differentially expressed resulting in primary (direct) and secondary (indirect) transcriptional outcomes. To identify more immediate and direct MOP1-dependent responses to ABA, we conducted a transcriptomic analysis using mop1-1 mutant and wild type plants treated with ABA for 1 hour. One hour of ABA treatment was sufficient to induce unique categories of differentially expressed genes (DEGs) in mop1-1. A comparative analysis between the two time-points revealed that distinct epigenetically-regulated changes in gene expression occur within the early stages of ABA induction, and that these changes are predicted to influence less immediate, indirect transcriptional responses. Homology with MOP1-dependent siRNAs and a gene regulatory network (GRN) were used to identify putative immediate and indirect targets, respectively. By manipulating two key regulatory networks in a temporal dependent manner, we identified genes and biological processes regulated by RdDM and ABA-mediated stress responses. Consistent with mis-regulation of gene expression, mop1-1 homozygous plants are compromised in their ability to recover from water deprivation. Collectively, these results indicate transcriptionally and physiologically relevant roles for MOP1-mediated regulation of gene expression of plant responses to environmental stress.